Measurement of the entrepreneurs of entrants to the faculty of Engineering Industrial of the UNMSM - Tinoco Gómez, Oscar (2008)
The purpose of the investigation was to determine the ability of students who venture entered the Faculty of Engineering in 2008 using the entrepreneurial skills, validated by Flores (UIGV, 2003). We also analyzed the factors that make difference in this capacity, such as the type of preparation for university, gender, or source of secondary school. The results suggest that students study subjects, according to the instrument used, have a high entrepreneurial skill